The Ashes of the Phoenix: Messianic Hope in British Eschatology after the Death of Henry Stuart - Givens, Bryan (Viator, 2024)
Abstract Henry Stuart, Prince of Wales (1594–1612), was the first British figure to be the subject of widespread hope as the “Lion of the North,” a Protestant version of the Last Emperor figure. As such, he would reform the Church and destroy the double Antichrists of evangelical apocalypticism— the pope and the Turks—and thereby usher in a reformed millennium. However, he died on November 6, 1612, at the age of eighteen, but the hopes he had engendered did not die with him. This essay will document the survival of the idea of a Protestant Last Emperor in British eschatology by examining the support for three men who were identified as the “heirs” of the prophetic hopes that had once surrounded Henry: Frederick V (1596–1632), Charles I (1600– 1649), and Gustavus Adolphus (1594–1632).